(untitled) (Fiep Bulletin - online, 2014)
The goal of the research is to identify ways of satisfaction or dissatisfaction of professionals in Physical Education with the new measures on the school evaluation adopted by Municipal Bureau of Education. Methodology: This is a qualitative research analysis which uses the contributions of the Review of Speech by Eni Orlandi. Sample three teachers of Physical Education operating in the fundamental teaching in the school system serving the City of Rio de Janeiro. All teachers who integrated the study point to ways of dissatisfaction with resolution 959.